THE EFFECTIVENESS OF INTEGRATED SCIENCE TEACHING MATERIALS ON THE THEME OF WEATHER AND ITS CHANGES: A STUDY OF READABILITY, CONCEPTUAL UNDERSTANDING, AND USER RESPONSES (TEACHERS AND STUDENTS) - Sari, Yuliana; Maulidia, Rachmani (Universitas Muhammadiyah Cirebon, 2025)
This study aims to examine the effectiveness of implementing integrated science teaching materials with the theme Weather and Its Changes in improving seventh-grade junior high school students’ conceptual understanding. The teaching materials were developed using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) combined with a didactic reduction approach to adjust the complexity of the content to students’ cognitive level. The research employed a Research and Development (R&D) method with a one-group pretest–posttest design. The participants consisted of 20 seventh-grade students from a private junior high school in Bogor Regency, 9 science teachers from Bogor City, and 2 expert validator teams. Research instruments included a readability test, a conceptual understanding test, student response questionnaires, and teacher response questionnaires. The results indicate that the readability level of the teaching materials was high, with percentages of 71% in Chapter I and 69% in Chapter II, both categorized as independent level. Students’ conceptual understanding improved with an N-Gain score of 0.40, which falls into the moderate category. Teacher responses were very positive, indicated by a CVI value of 0.85, categorized as highly feasible. Student responses also showed strong acceptance, with 61.4% agreed and 34.2% strongly agreed on the feasibility of the teaching materials. The findings suggest that the developed integrated science teaching materials are effective in improving students’ conceptual understanding and feasible to be used as independent learning resources. Their effectiveness is influenced by attractive visual design, contextual phenomena, and systematic organization of the content. This study highlights the importance of integrating a didactic reduction approach in developing science teaching materials suited to junior high school students’ cognitive characteristics.